Pemberdayaan Kelompok Wanita Tani Cendawan 31 Melalui Peningkatan Produksi Sayuran Dan Pendapatan Di Kota Pangkalpinang - Eni Karsiningsih; Andini Meisya Sriwijayani Suwardih; Dinda Aulia; Santia Santia; Sulthon A’uliya Alfarissi; Gita Ardianta; Aprilianti Wulandari; Annisa Miswarni Lubis; Dodi Irwandi; Muhammad Ferghio Jovanka (Pakis Journal Institute, 2024)
The concept of urban farming refers to the practice of farming in urban areas, which is usually done on limited land such as house yards, rooftops or vacant lots in the city. Urban farming aims to meet the very high food needs of urban communities when there is a scarcity of land for food production in urban areas. The demand for vegetables is not matched by vegetable production, resulting in inflation. Some of the obstacles faced by KWT Cendawan 31 include: vegetable farming is not yet commercially oriented, management is still simple, motivation and awareness of members are still low, production patterns are not well planned, vegetable price information is still limited, marketing channels are not efficient and simple and limited promotion of vegetable products. This farmer women group empowerment program aims to increase vegetable production & income. The methods used in this program are active participatory methods, mentoring and counseling on vegetable production processes from upstream to downstream. The success of the work program carried out was able to overcome the problem of the lack of creativity and innovation of the Cendawan 31 Women Farmers Group (KWT) in developing the planting of types of vegetables, the low production of vegetables in the area of the Cendawan 31 Women Farmers Group (KWT) and being able to arrange a planting schedule, choosing the right type of plant and rotating the planter.